BENTUK DAN FUNGSI TINDAK TUTUR ILOKUSI SERTA PERLOKUSI DALAM TUTURAN FILM AGAK LAEN KARYA MUHADKLY ACHO: KAJIAN PRAGMATIK - Nabila Retno Indah Hapsari; Riris Tiani (Jurnal Ilmiah Multidisiplin Ilmu, 2025)
Cinematography can be seen as a manifestation of contemporary literature that not only provides entertainment but also serves as a vehicle for transmitting messages related to social dynamics. Muhadkly Acho's film Agak Laen was chosen as the subject of this study because it contains a wealth of pragmatic aspects that are manifested through the dialogues of its characters. This study aims to reveal the form and function of illocutionary and perlocutionary speech acts, as well as to examine the use of sentences based on suprasegmental characteristics, including intonation, stress, and pauses, in the analyzed utterances. The approach used is pragmatic, based on John R. Searle's theory of speech acts, which classifies illocution into five categories, while perlocution focuses on the implications that arise. The research methodology is descriptive qualitative with data collection techniques through observation and note-taking, then analyzed contextually. The research findings show that the film Agak Laen contains various forms of illocutionary speech acts, with a dominance of the directive and expressive categories. The characters often use indirect speech as a strategy to evoke humorous effects or subtle satire. The conclusion of this study indicates that the dialogue in the film not only articulates denotative meaning but also implies implicit meaning that enriches the pragmatic dimension of interaction between characters.